(untitled) (Revista Nacional de Odontología, 2022)
Introduction: gingival melanosis physiology is the abnormal deposit of melanin in the gum, it is not considered a pathology. However, it is an aesthetic and psychological problem for some people, requiring treatment. There are some therapeutic alternatives for depigmentation, among which is the application of trichloroacetic acid, which is not invasive. Case report: 35-year-old female patient, who presented physiological gingival melanosis, which generated aesthetic problems in the smile and psychosocial problems with coworkers, was treated with 80% trichloroacetic acid, with positive results. Conclusion: gingival depigmentation with trichloroacetic acid in physiological gingival melanosis is a conservative, effective and little traumatic treatment alternative.